Examining the Effect of Organizational Culture on the Relationship between Supply Chain Quality Management Practices Adoption and Performance of Private Hospitals in Kenya - Ondiek, Tobias Okoth; Odock, Stephen; Njihia, James Muranga; K’Obonyo , Peter (European Scientific Journal, ESJ, 2020)
Health care institutions have complex global supply networks and organizations that have heterogenous cultural configurations. There are a number of studies that have directly linked supply chain quality management practices in the manufacturing sector and other service firms to organizational performance. However, minimal research has been done to examine the role of corporate culture in the relationship. Moreover, there is need to empirically confirm effect of corporate culture in private hospitals in Kenya where provision of quality and affordable health care remains a challenge. Corporate culture fit between organizations serves as a thread that ties firms together. The study was conducted in order examine the effect of organizational culture on the relationship between supply chain quality management practices adoption and performance of private hospitals in Kenya. Positivist research orientation and descriptive cross-sectional research design guided the research process. Raw data was collected from management staff tasked with supply chain decision making responsibility in the hospitals. A response rate of 70.51% was realized. Normality, collinearity, homoscedasticity and autocorrelation constituted model diagnosis. Hypothesis was tested using model fit indices and significance of path coefficient. The findings indicate that corporate culture has significant positive effect on the relationship. The study concluded that right corporate culture among supply chain partners both internally and externally serves as catalyst while implementing SCQM practices to bring about improved performance. It is therefore recommended that for private hospitals to benefit more from improved performance upon adopting SCQM practices, they must ensure homogeneity of cultural configurations internally and externally. In addition, the study provides future researchers with a useful conceptual and methodological reference that can be used in the pursuit of further studies particularly in the area of both supply chain and quality management with specific reference to the corporate culture as a moderating variable.